Corporate social responsibility and public accountability - Filios, Vassilios P. (Journal of business ethics, 1984)
The development of legislation determining corporate behaviour is a fascinating topic, offering insight into the societal problems of corporate enterprise as they are related to their accounting, their administration, and their external reporting. In this paper the following specific implications for accounting are examined:, -Should accountants get involved in social auditing and are they the ‘core’ persons in corporate social accounting systems?, -Should corporate social performance measurement and reporting become obligatory and to what extent?, -A general framework for the implementation of corporate social accounting systems is suggested and quidelines for its auditing are proposed., -A tentative set of social auditing standard is outlined together with its methodological accompaniments.